Redefining Curepe Junction Based on User Perception - Dass, Deena (My University, 2022)
Development at transportation hubs throughout Trinidad and Tobago utilises antiquated strategies to resolve complex transportation engineering and urban design elements (TEUD), neglecting the input from the end-users. The objectives of this research were accomplished by utilising the user perception to identify the problematic TEUD elements of Curepe Junction, developing the design guidelines and assessing the potential impacts of the redesign. In pursuance of designing a successful junction, the leading successful space concepts were explored, i.e. Complete Streets, Context Sensitive Solution and Portals to Places. Three core elements were identified upon connecting these concepts: the people, the furnishings, and the network. While assessing these elements in the context of Curepe Junction, 125 hub users deemed all the elements of this auto-centric junction as below acceptable levels, identifying the most problematic elements as: 1. Accessibility for the elderly and people with disabilities 2. Accessibility of transit information 3. Convenient and comfortable seating accommodations Upon redesigning the junction on the advice of the hub users and guided by literature utilising successful space concepts, the redesign generated a higher hub user satisfaction rate than the current design. This paradigm shift of redesigning for the people, by the people, illustrated that successful spaces thrive on the involvement of the end-users, ensuring the development of sustainable and practical design guidelines. Thus, concluding that the success of a space is directly proportional to the extent of the user involvement.
Keywords: Transportation Engineering; Urban design; Place Diagram; Trinidad and Tobago